PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN DEWAN KOMISARIS INDEPENDEN SEBAGAI VARIABEL PEMODERASI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Padmayanti, Ni Putu Enny Widhi; Suryandari, Ni Nyoman Ayu; Munidewi, I.A. Budhananda (Jurnal Riset Akuntansi (JUARA), 2019)
The value of the company describes a state of the company, with the high value of thecompany will be followed by the high prosperity of shareholders. Company value is reflected inthe company’s stock price. High corporate values can be predicted using information containedin financial statements and corporate governance mechanisms within the company. This studyaims to reexamine the effect of the variable return on assets and leverage on firm value with anindependent board of commissioners as a moderating variable.The sample in this study were70 manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2017.Determination of samples using purposive sampling method. The analytical tool used is moderateregression analysis.The results of the study indicate that the return on assets variable doesnot affect the value of the company. The leverage variable also does not affect the value of thecompany. Independent commissioner variables are able to strengthen the relationship betweenROA and company value. But the independent board of commissioners is not able to moderatethe relationship between leverage and company value.